The impact of laparoscopic gynecological surgery training on the technicity index of a developing country center - Spadoto-Dias, Daniel [UNESP]; Bueloni-Dias, Flávia Neves [UNESP]; Modotti, Waldir Pereira; França, Maria Laura Marconi [UNESP]; Chihara, Rodrigo Takeshi [UNESP]; Chauvet, Pauline; Rabischong, Benoit; Botchorishvili, Revaz; Bourdel, Nicolas; Canis, Michel (FapUNIFESP (SciELO), 2023)
Purpose: To compare laparoscopic gynecological surgery training between a developed country’s reference center (host center) and a public reference service in a developing country (home center), and use the technicity index (TI) to compare outcomes and to determine the impact of laparoscopic gynecological surgery fellowship training on the home center’s TI. Methods: The impact of training on the home center was assessed by comparing surgical performance before and after training. TI was assessed in 2017 in the host center, and before and after training in the home center. Epidemiological and clinical data, and information on reason for surgery, preoperative images, estimated intraoperative bleeding, operative time, surgical specimen weight, hospital stay length, complication and reintervention rates were collected from both institutions. Home center pre-training data were retrospectively collected between 2010 and 2013, while post-training data were prospectively collected between 2015 and 2017. A two-tail Z-score was used for TI comparison. Results: The analysis included 366 hysterectomies performed at the host center in 2017, and 663 hysterectomies performed at the home center between 2015 and 2017. TI in the host center was 82.5%, while in the home center it was 6% before training and 22% after training. There were no statistical differences in length of hospital stay, preoperative uterine volume, surgical specimen weight and complication rate between centers. However, significantly shorter mean operative time and lower blood loss during surgery were observed in the host center. Conclusion: High-quality laparoscopic training in a world-renowned specialized center allowed standardizing laparoscopic hysterectomy procedures and helped to significantly improve TI in the recipient’s center with comparable surgical outcomes.
Keywords: Developing Countries; Education, Medical, Continuing; Hysterectomy; Index; Laparoscopy; Public Health Systems Research